Many waters - L'Engle, Madeleine (New York Square Fish, 2007)
The fifteen-year-old Murry twins, Sandy and Dennys, are accidentally sent back to a strange Biblical time period, in which mythical beasts roam the desert and a man named Noah is building a boat in preparation for a great flood
Sequel to: A swiftly tilting planet
13
Keywords: Noah -- (Biblical figure) -- Juvenile fiction; Noah -- (Biblical figure) -- Fiction; Fantasy; Noah's ark -- Fiction; Time travel -- Fiction; Twins -- Fiction